Problems Faced by Students in Group Discussion at Eed of UMY - Noor Muhammad Fadhilah Yasien (PBI 15 UMY 061, 2015)
*61 Group discussion is commonly used by English Education Department (EED) teachers at Universitas Muhammadiyah Yogyakarta (UMY) as a teaching method. In the group discussion, students are required to be active in giving their opinions. Unfortunately, based on the researcher’s experience and observation, many students seemed to have difficulty to deliver their idea freely and as the result they tended to keep silent during the discussion. This research intended to find out the obstacles that the learners faced in group discussion at EED of UMY. Furthermore, this research investigated the problems existing in group discussion to EED’s students. The researcher used qualitative method to answer the research problem. In collecting the data, an interview was conducted by the researcher. Three students in batch 2013 at EED of UMY were chosen as the participants who had been encountering the group discussion implementation for at least two years. The result of this research showed that the main problems that students faced in group discussion were related to motivation. The examples of motivational issues associated with group discussion at EED of UMY were free rider and social loafing, ethnic and cultural background, and social dilemma that influenced the lost motivation toward the students. This research also revealed the role of teacher in the perspective of students in implementing the interest group discussion. After a thorough analysis, a recommendation has been made for the teachers and learners to suggest as a consideration and an evaluation.